Du point à l'espace (rural) : localisation de mentions textuelles et mise à l'épreuve de normes socio-spatiales - Nicolas Poirier (Bulletin du Centre d’Études Médiévales d’Auxerre)
Geolocation of ancient sources is a challenge to historians and archaeologists who aims to adopt a spatial approach to their object of study. Known biases affecting the corpus of sources that have survived can often be considered prohibitive to any spatial approach of their contents. Worse, these same biases, whether related to production conditions, hazards of conservation or vagaries of counting, can discourage any attempt of quantitative analysis of these data. This paper proposes two different aspects of spatial analysis through the implementation of modern and medieval written sources, both of which sharing a common ground investigation. The first part concerns the presentation of a methodology for use of textual citations identified in serial sources in order to highlight the medieval and modern dynamics affecting the landscape and settlement. The second part concerns the study of space standards and organizational models described by the written sources that it is possible to test by the use of spatial analysis tools.